Scalp necrosis and giant cell arteritis: case report and issues in wound management - Landis, Stefan J (Int Wound J, 2005)
Scalp necrosis is rare in patients with giant cell arteritis. Here, we report the case of an 81‐year‐old woman who presented with a management problem that required a truly multidisciplinary approach to treatment. A combined approach of effective wound bed preparation with selective debridement, prolonged antimicrobial therapy, corticosteroid use and careful dressing choices resulted in a successful outcome in a potentially disastrous situation.